1995
DOI: 10.1007/bf01874761
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of nematodes and soil-borne fungi fromAmmophila arenaria (Marram grass) in Dutch coastal foredunes by multivariate techniques

Abstract: A survey was carried out at nine locations in the Dutch coastal foredunes to identify the species of soil borne fungi and nematodes associated with Ammophila arenaria (Marram grass). Ammophila arenaria is a sand binding grass that is very important for the stabilization of coastal foredunes. Degeneration of the plants occurs at stabilized sites and is supposed to be caused by a combination of soil-borne fungi and nematodes. Canonical correspondence analysis (CCA) and two-way indicator species analysis (TWlNSPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 19 publications
2
40
0
Order By: Relevance
“…The specificity of soil pathosystems from successional foredune plants, although demonstrated by bioassays ( Van der Putten et al 1993) has not yet been elucidated. In both H. rhamnoides and A. arenaria, a number of plant parasitic nematodes and plant pathogenic fungi may be involved (Zoon et al 1993, De Rooij-Van der Goes et al 1995a). The competition experiments showed that sedentary endoparasitic nematodes (Heterodera avenae group) may contribute to the specificity of the pathosystem, as they formed cysts on roots of A. arenaria, but not on F. rubra.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The specificity of soil pathosystems from successional foredune plants, although demonstrated by bioassays ( Van der Putten et al 1993) has not yet been elucidated. In both H. rhamnoides and A. arenaria, a number of plant parasitic nematodes and plant pathogenic fungi may be involved (Zoon et al 1993, De Rooij-Van der Goes et al 1995a). The competition experiments showed that sedentary endoparasitic nematodes (Heterodera avenae group) may contribute to the specificity of the pathosystem, as they formed cysts on roots of A. arenaria, but not on F. rubra.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on soil-borne pathogens in natural vegetation are mainly confined to coastal sand dunes (Oremus and Otten 1981, Van der Putten et al 1993, Zoon et al 1993, De Rooij-Van der Goes et al 1995a, tropical rain forests (Augspurger 1990), and old fields (Bever 1994). The presence of specific soil pathogens in a successional sere of plants in coastal sand dunes (Van der Putten et al 1993) should have consequences for competitive interactions among the successive plant species (Crawley 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial inocula from both rhizosphere soils were prepared using the following protocol: 1 g Goes et al, 1995). In order to make sure that 163 no bacterial contamination was introduced together with the fungi, both fungi were pre-164 cultured on PDA containing oxy-tetracycline (50 mgL -1 ) and streptomycine (100 mgL -1 ).…”
mentioning
confidence: 99%
“…They are able to strongly decrease the biomass of A. arenaria (de Rooij van der Goes 1995a), if not controlled by their microbial enemies (Piśkiewicz et al 2007). In the field T. ventralis usually does not reach population levels that can affect plant growth (van der Stoel et al 2002), but numbers vary locally (de Rooij van der Goes et al 1995b). In the present study, we examine if plant ectoparasitic nematodes T. ventralis are able to sense and avoid microbial communities that include their natural antagonists.…”
Section: Introductionmentioning
confidence: 99%